Salvinorin A Inhibits Airway Hyperreactivity Induced by Ovalbumin Sensitization - Rossi, Antonietta; Caiazzo, Elisabetta; Bilancia, Rossella; Riemma, Maria A.; Pagano, Ester; Cicala, Carla; Ialenti, Armando; Zjawiony, Jordan K.; Izzo, Angelo A.; Capasso, Raffaele; Roviezzo, Fiorentina (Frontiers in Pharmacology, 2017)
Salvinorin A, a neoclerodane diterpene isolated from Salvia divinorum, exerts a number of pharmacological actions which are not solely limited to the central nervous system. Recently it has been demonstrated that Salvinorin A inhibits acute inflammatory response affecting leukotriene (LT) production. Since LTs are potent lipid mediators implicated in allergic diseases, we evaluated the effect of Salvinorin A on allergic inflammation and on airways following sensitization in the mouse. Mice were sensitized with s.c. injection of ovalbumin (OVA) on days 1 and 8. Sensitized mice received on days 9 and 12 on the shaved dorsal surface air administration to induce the development of the air-pouches. On day 15 animals were challenged by injection of OVA into the air-pouch. Salvinorin A, administered (10 mg/kg) before each allergen exposure, significantly reduced OVA-induced LT increase in the air pouch. This effect was coupled to a reduction in cell recruitment and Th2 cytokine production. In another set of experiments, mice were sensitized with OVA and both bronchial reactivity and pulmonary inflammation were assessed. Salvinorin A abrogated bronchial hyperreactivity and interleukin (IL)-13 production, without effect on pulmonary inflammation. Indeed cell infiltration and peribronchial edema were still present following diterpenoid treatment. Similarly, pulmonary IL-4 and plasmatic IgE levels were not modulated. Conversely, Salvinorin A significantly reduced LTC4 production in the lung of sensitized mice. Finally mast cell activity was evaluated by means of toluidine blue staining. Data obtained evidenced that Salvinorin A significantly inhibited mast cell degranulation in the lung. Our study demonstrates that Salvinorin A inhibits airway hyperreactivity induced by sensitization by inhibition of LT production and mast cell degranulation. In conclusion Salvinorin A could represent a promising candidate for drug development in allergic diseases such as asthma.